Enhanced supercapacitive performance of cost-effectively synthesized ZnO-reduced graphene oxide composite. Issue 12 (12th August 2016) - Majeed, A.; Anwar, A. W.; Ullah, W.; Aziz, T.; Sharif, R.; Sharif, A.
Abstract : Commercially accessible and long-lasting resources of energy are among the foremost areas of current research. Supercapacitors have taken the position of very thoughtful candidates in the energy-storing field to meet the modern necessities. Several graphene-based materials have been employed for supercapacitor electrodes. Here, we demonstrated an economical and advanced hydrothermal technique using combination of two reducing materials (urea and starch) for the fabrication of reduced graphene oxide/zinc oxide (RGO/ZnO) composite. The X-ray diffraction and scanning electron microscopy analysis were carried out to study the structure and of RGO/ZnO composite. The supercapacitive behaviour of RGO/ZnO composite was studied via cyclic voltammetry and galvanostatic charge/discharge experiments. The results showed enhanced specific capacitance (313.14 F g −1 ) with good cyclic stability (1000 cycles).